(untitled) (Palaeohispanica. Review about languages and cultures of Ancient Hispania, 2019)
We here present thirteen graffiti on ceramic vessels recovered from the various archaeological sites of Cabrera de Mar. Unfortunately, the inscriptions are short, all of one or two signs, but attest to the use of the Iberian script in the Cabrera de Mar valley during the 2nd and 1st centuries BC, and confirm that the inhabitants of Ilduro used the Iberian language until at least the first half of the 1st century BC.